China's assertive posture in reinforcing its territorial and sovereignty claims in the South China Sea: an insight into Malaysia's stance - Ahmad, Mohammad Zaki; Mohd Sani, Mohd Azizuddin (Cambridge University Press, 2017)
China's growing assertiveness in strengthening its territorial and sovereignty claims in the South China Sea has arguably intensified friction and deepened tension between the rival claimant States. In sharp contrast to the strong reactions of its fellow ASEAN claimants, such as Vietnam and the Philippines, Malaysia traditionally has been less critical and more inclined to downplay China's perceived emotive actions. This subtle foreign policy orientation is likely to remain unchanged in the immediate future. Malaysian leaders are aware of the need to continue adopting a more cautious but pragmatic approach to counter China's increasingly aggressive actions in the Spratly Islands. Because of the significant economic and political benefits derived from its close relationships with China, Malaysia's policy preference is aimed to avoid jeopardizing such relations. However, the growing presence of Chinese military vessels in Malaysia's waters in recent years has forced the latter to reassess its foreign policy approach, which might include adopting a more assertive stance towards China. Set against this backdrop, this article aims to give an exploratory insight into Malaysia's external behaviour and actions in response to China's recent growing aggressiveness in the South China Sea. To this end, the aim of this article is achieved through a twofold approach. First, it examines Malaysia's overlapping claims to maritime features and waters with China, with the focus on the Spratly Islands group. Lastly, the article provides an explorative insight of Malaysia's rationalist stance, particularly under the current administration of Prime Minister Najib Tun Razak, in response to China's aggressiveness. It also examines the motivations, intentions, and basis of this external posture.